(untitled) (Eurasian Journal of Ecology, 2016)
In this study, results of porosity, chemical composition and the sorption capacity of the wheat husk made sorbent and also results of the cleaning efficiency of waste waters from heavy metals by sorbent were obtained. Namely, sorption capacity for Cd, Cu, Pb, Fe, Zn metals versus time